LYTIC SERIES OF TYPE JOBOIDE PALEOINDIAN PERIOD, FROM PARAGUANA PENINSULA OF VENEZUELA NOR-WEST, IN THE COLLECTION OF THE MUSEUM OF ARCHAEOLOGY AND ANTHROPOLOGY OF NATIONAL UNIVERSITY OF SAN MARCOS - Yataco, Juan (2012)
The research of twenty seven archaeological pieces from collection of Venezuela Republic conserved in San Marcos University Museum in the Archaeological and Anthropological San Marcos University Museum, put in evidence the presence of bifacial performs, debris, stone tools and points of quarzites type. These have been determined the type Joboide (13.664 calBC-14.850 calBC) coming from cerro Santa Ana, Peninsula de Paraguaná. Due to be the only unique collection in Peru and their Joboide association, we have proceeded to relate their temporal association with the radiocarbon dates obtained from Taima-Taima site using the radiocarbon calibration.